HERKUNFT UND ENTWICKLUNG DES KIRCHLICHEN CHORGESANGS IN DEN RUMÄNISCHEN LÄNDERN UND SIEBENBÜRGEN. MUSIKOLOGISCHE PERSPEKTIVEN - BRIE, Mihai (Studia Universitatis Babes-Bolyai Musica, 2019)
Origin and Development of Church Choral Singing in the Romanian Countries and Transylvania. Musicological Perspectives. The church music culture in the Carpathian-Danubian-Pontic area was a reference in the Eastern European landscape. In the nineteenth century there was another musical orientation, the polyphonic one, specific to Europe centuries ago, for which this polyphonic musical introduction bears the imprints of a civilization worthy of consideration in the context of the European polyphonic musical civilization. The present scientific expertise highlights personalities who throughout their lives have been creating the polyphony line for all time. In this study we highlight the contribution, contribution and dedication of each in the valorization of the incipient native polyphonic heritage.